2018
DOI: 10.1007/s11064-018-2530-y
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid Protects 6-OHDA Induced Neurotoxicity by Attenuating Oxidative Stress in Human Dopaminergic Cell Line

Abstract: Gallic acid is one of the most important polyphenolic compounds, which is considered an excellent free radical scavenger. 6-Hydroxydopamine (6-OHDA) is a neurotoxin, which has been implicated in mainly Parkinson's disease (PD). In this study, we investigated the molecular mechanism of the neuroprotective effects of gallic acid on 6-OHDA induced apoptosis in human dopaminergic cells, SH-SY5Y. Our results showed that 6-OHDA induced cytotoxicity in SH-SY5Y cells was suppressed by pre-treatment with gallic acid. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 38 publications
1
33
1
Order By: Relevance
“…In this study, 6-OHDA caused a substantial inhibition in GPx activity that was not observed in presence of methanolic fraction. Similar data were demonstrated in neuroblastoma cells treated with 6-OHDA [ 45 ]. In PD patients, the degree of symptom severity correlates with intracellular GSH loss in substantia nigra [ 46 ].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, 6-OHDA caused a substantial inhibition in GPx activity that was not observed in presence of methanolic fraction. Similar data were demonstrated in neuroblastoma cells treated with 6-OHDA [ 45 ]. In PD patients, the degree of symptom severity correlates with intracellular GSH loss in substantia nigra [ 46 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, treatment with common antioxidants such as vitamin C, vitamin E, and coenzyme Q10 exhibited poor effects in disease delay. For this reason, the search for either synthetic or other natural substances with rich biological properties and complex multi-target mechanisms continue for effective therapy or the prevention of PD [82,83].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they also found that GA could enhance the thermal stability of Keap1 and compete with Nrf2 for Keap1 . In the study by Chandrasekhar et al., GA pretreatment could reverse the up‐regulation of caspase‐3, Keap1, and down‐regulation of Nrf2 induced by 6‐OHDA, and protect nerve cells from 6‐OHDA‐induced injury . Chicoric acid (CRA, 15 ) is from Cichorium glandulosum Boiss .…”
Section: Natural Polyphenols Nrf2 Activators In Multiple Disease Modelsmentioning
confidence: 99%